Algebraic formulas –
§ a2 –
b2 = (a – b)(a + b)
§ (a+b)2 =
a2 + 2ab + b2
§ a2 +
b2 = (a – b)2 +
2ab
§ (a – b)2 =
a2 – 2ab + b2
§ (a + b
+ c)2 = a2 + b2 +
c2 + 2ab + 2ac + 2bc
§ (a – b
– c)2 = a2 + b2 +
c2 – 2ab – 2ac + 2bc
§ (a + b)3 =
a3 + 3a2b + 3ab2 +
b3 ; (a + b)3 =
a3 + b3 + 3ab(a + b)
§ (a – b)3 =
a3 – 3a2b + 3ab2 –
b3
§ a3 –
b3 = (a – b)(a2 +
ab + b2)
§ a3 +
b3 = (a + b)(a2 –
ab + b2)
§ (a + b)3 =
a3 + 3a2b + 3ab2 +
b3
§ (a – b)3 =
a3 – 3a2b + 3ab2 –
b3
§ (a + b)4 =
a4 + 4a3b + 6a2b2 +
4ab3 + b4)
§ (a – b)4 =
a4 – 4a3b + 6a2b2 –
4ab3 + b4)
§ a4 –
b4 = (a – b)(a + b)(a2 +
b2)
§ a5 –
b5 = (a – b)(a4 +
a3b + a2b2 + ab3 + b4)
§ If n is
a natural number, an – bn = (a – b)(an-1 +
an-2b+…+ bn-2a + bn-1)
§ If n is
even (n = 2k), an +
bn = (a + b)(an-1 –
an-2b +…+ bn-2a – bn-1)
§ If n is
odd (n = 2k + 1), an +
bn = (a + b)(an-1 –
an-2b +…- bn-2a + bn-1)
§ (a + b
+ c + …)2 = a2 + b2 +
c2 + … + 2(ab + ac + bc + ….
§ Laws of
Exponents
(am)(an) = am+n
(ab)m = ambm
(am)n = amn
Fractional Exponents
a0 = 1
am / a n=a m−n
a0 = 1
am / a n=a m−n
am = 1/
a−m
a−m = 1 / am
a−m = 1 / am
No comments:
Post a Comment